SMALL BENTHIC FORAMINIFERA AS AN INDICATOR OF PALEOTSUNAMI IN UJUNGKULON, BANTEN PROVINCE, INDONESIA - Fitriany, Ria; Jurnaliah, Lia; Iskandarsyah, T. Y. Waliana Muda (Faculty of Geological Engineering, Universitas Padjadjaran, 2019)
Research area is located at 1050 27” 6,99” E and 60 50’ 1,29” S. The purpose of this research is to know the diversity of small benthic foraminifera on “X” core, Ujung Kulon, Banten Province, Indonesia. Sixteen sediment samples (paleotsunami deposits) from research area were analyzed to collect small benthic foraminifera. Sediment samples are coastal sediment that were taken from one drill point by using shallow drill to a depth 240cm from the ground. Sampling for analyses small benthic foram was conducted in each layer sediment. At this stage, sequence of layers and the thickness of sediment were observed. In order to separate the sediments and the foraminifera, sediment samples were treated using Hydrogen Peroxide method. Small benthic foraminifera data is collected by using quantitative method. The number of species and individuals were counted in every 1 gram dry sample. Analyses of small benthic foraminifera shows there are 55 species small benthic foraminifera and 43.866 specimen. The dominance species is Planulina wuellerstorfi which is a deep marine species. Furthermore, The Sannon-Wiever diversity index of all sample are low. It can be concluded that was a paleotsunami.